Improving coffee sector Climate-Smart Awareness and decision-making - International Institute of Tropical Agriculture; Olam (2018)
The Institute of International Agriculture (IITA) and Olam are working together in the Mt. Elgon region in Uganda to develop climate-smart agricultural (CSA) practices to help farmers to manage the specific effects of weather variability/climate change to that region and lay them out in a “Stepwise” pathway tailored to specific farmer segments to help them make smarter and more timely investment in resilience building practices. Olam, a coffee trader in Uganda, offering direct services to its farmers, sees the project value in its ability to save costs in the short-term while building farmer climate resilience in the long-term, all the while creating a more sustainable supply.